Disrupting a Plasmodium berghei putative phospholipase impairs efficient egress of merosomes. Issue 8 (July 2022) - Srivastava, Pratik Narain; Mishra, Satish
Graphical abstract: Highlights: Plasmodium berghei phosphatidic acid (PA) preferring phospholipase A1 ( Pb Pla1) localizes in cytosol. Pb Pla1 is dispensable in blood and mosquito stages. PbPla1 − sporozoites show compromised in vivo infectivity. PbPla1 − parasites have a defect in merosome egress. Abstract: Merosome development is a very important part of the Plasmodium life cycle. It constitutes the last step of liver stage development after which merozoites egress to the bloodstream and invade red blood cells. Many parasite proteins have been shown to play key roles in this process. Phospholipases are known to be actively involved in membrane formation and remodeling. At least one phospholipase A2, localized to the parasitophorous vacuolar membrane, is known to be directly important for parasitophorous vacuolar membrane (PVM) rupture and subsequent release of merozoites. Here, we characterize a Plasmodium berghei phosphatidic acid (PA) preferring phospholipase A1 ( Pb Pla1) homolog. C-terminal 3XHA-mCherry tagging revealed that Pb Pla1 is expressed in all life cycle stages except sporozoites and is present in the parasite's cytoplasm. Targeted disruption of PbPla1 revealed its non-essentiality for the blood and mosquito stages. Pla1 − sporozoites were found to be late in their ability to establish successful blood stage infection in mice. While exoerythrocytic form development was found to be normal in vitro, a decrease in the number of merosomes was observed. PVM rupture in late exo-erythrocytic forms (EEFs) was quantified by counting the number of parasites with intact PVMs, and was found to be significantly higher in Pla1 − . Our findings indicate the role of Pb Pla1 in merosome release.